2013
DOI: 10.1002/clc.22093
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Seattle Heart Failure Model and Cardiopulmonary Exercise Capacity for Prediction of Death in Patients With Chronic Ischemic Heart Failure and Intracoronary Progenitor Cell Application

Abstract: Background: Despite many therapeutic advances, the prognosis of patients with chronic heart failure (CHF) remains poor. Therefore, reliable identification of high-risk patients with poor prognosis is of utmost importance. Cardiopulmonary exercise testing (CPET) provides important prognostic information by peak O 2 uptake (peak VO 2 ), maximal oxygen pulse (O 2 Pmax), O 2 uptake efficiency slope (OUES), and VE/VCO 2 slope (VE/VCO 2 ). A different approach for prognostic assessment is the Seattle Heart Failure M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…15 Median follow-up was 1673 days, interquartile range (IQR) [923,1828]. The primary endpoint was defined as allcause mortality and was confirmed by reviewing death certificates or contacting relatives or family physicians as previously described.…”
Section: Follow-up and Clinical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Median follow-up was 1673 days, interquartile range (IQR) [923,1828]. The primary endpoint was defined as allcause mortality and was confirmed by reviewing death certificates or contacting relatives or family physicians as previously described.…”
Section: Follow-up and Clinical Characteristicsmentioning
confidence: 99%
“…The primary endpoint was defined as allcause mortality and was confirmed by reviewing death certificates or contacting relatives or family physicians as previously described. 15 Median follow-up was 1673 days, interquartile range (IQR) [923,1828].…”
Section: Follow-up and Clinical Characteristicsmentioning
confidence: 99%
“…In line with these results, a very recent report including 2331 patients demonstrated that ICD use was associated with a 37% reduction in all‐cause mortality ( P = 0.002) after adjustment for the clinical risk profile, performed by means of the Seattle Heart Failure Model (SHFM) . The SHFM is a comprehensive scoring system, developed and validated in large HF patient datasets, which has excellent prognostic efficacy and the ability to differentiate among various modes of death . The SHFM has been shown to predict all‐cause mortality.…”
Section: Fundingmentioning
confidence: 71%
“…In heart failure patients, prognostic models like the Seattle Heart Failure Model (SHFM) and the Meta‐Analysis Global Group in Chronic (MAGGIC) Heart Failure score are widely used [13] , [14] , [15] , [16] . However, only limited data exist about the prognostic accuracy of these scores in patients referred for TMVR [17] .…”
Section: Introductionmentioning
confidence: 99%